2012
DOI: 10.1120/jacmp.v13i5.3271
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into factors affecting electron density calibration for a megavoltage cone‐beam CT system

Abstract: There is a growing interest in the use of megavoltage cone‐beam computed tomography (MV CBCT) data for radiotherapy treatment planning. To calculate accurate dose distributions, knowledge of the electron density (ED) of the tissues being irradiated is required. In the case of MV CBCT, it is necessary to determine a calibration‐relating CT number to ED, utilizing the photon beam produced for MV CBCT. A number of different parameters can affect this calibration. This study was undertaken on the Siemens MV CBCT s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
(50 reference statements)
0
10
0
Order By: Relevance
“…Dose calculations using MV CBCT images are feasible (1,2) . However, consistently converting CT numbers to electron density can be difficult (3–6) . Previous research studies reported a gamma index of 98% for 3% and 3 mm criteria that described dose calculation accuracy on MV CBCT for head‐and‐neck cases, using in‐house developed image correction filters (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Dose calculations using MV CBCT images are feasible (1,2) . However, consistently converting CT numbers to electron density can be difficult (3–6) . Previous research studies reported a gamma index of 98% for 3% and 3 mm criteria that described dose calculation accuracy on MV CBCT for head‐and‐neck cases, using in‐house developed image correction filters (7) .…”
Section: Introductionmentioning
confidence: 99%
“…[1] pCT-kVCBCT Calibration curves have been observed to be very stable over a period of eight consecutive weeks. [23] Various image correction methods have been used, and dose variations observed to be in the range −0.23-0.69% of pCT doses.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT has been used to perform dose-of-the day computations but was dependant on dedicated research software for image registration. [ 1 2 3 4 ] CATPhan and CIRS phantoms have been confined to Quality Assurance purposes, therefore, the possibility of using those phantoms as part of dosimetric calculations have been overlooked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Additionally, the increased interest in the use of MVCT data for treatment planning requires knowledge of the electron density of the tissues and checking how the structures of different densities are delineated by different observers. 10 …”
Section: Introductionmentioning
confidence: 99%